(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The housekeeping department is the most important part of a resort because they are responsible for the cleanliness, and they take satisfaction in keeping the resort comfortable, to build the ‘home away from home.’ Effective housekeeping can help to oversee and extinguish resort hazards. It is not just about cleanliness; it keeps work and guest areas organized and in order. This study aims to identify what cleaning chemical supplies are needed in training activities in a resort and what adjustments are made if the cleaning chemicals and supplies are not available to enhance customer satisfaction. Customer satisfaction can be enhanced in terms of the employee’s performance, cleanliness, comfort, and guest satisfaction. However, there are problems encountered by the customers, such as customer complaints occurring because of some problem inside the guest room (malfunctioning air conditioning unit, clogged toilet, TV signal, etc...), but solutions have been made, including regular room check-ups and maintenance. To gain more knowledge and recognize what to do if there are not enough cleaning chemicals and equipment in the resort, they have to maintain organized housekeeping supplies. Use this study to gain a basic understanding of the importance of cleaning supplies that they could use in the future. Housekeepers will be able to get enough information to use for their work as they improve and know better about working hours. This study is to gather information about housekeeping cleaning supplies and what practices are needed to have successful duties.